Zakat Management Strategy at the National Zakat Agency in Makassar City - Aisyah, Sitti Noor; Siti Rukayyah, Hasniaty Hasniaty , (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the zakat management strategy at the National Zakat Agency (Baznas) of Makassar City using SWOT analysis. The results of the study indicate that Baznas Makassar City is in the aggressive quadrant, which means it has great internal strength and external opportunities that can be utilized to improve zakat management. The proposed strategies include optimizing technology in zakat management, such as the use of online zakat platforms to increase transparency and efficiency, as well as strengthening productive zakat which aims to empower mustahik to be more economically independent. In addition, Baznas is expected to strengthen collaboration with various parties such as the government and the private sector, as well as increase education and socialization to the community regarding the importance of zakat. With these strategies, Baznas Makassar City can be more effective in managing zakat and improving community welfare. Keywords: Zakat Management, Baznas Makassar City, SWOT Analysis